HUBUNGAN ANTARA PERSEPSI KETERAMPILAN BELAJAR DAN PRESTASI AKADEMIK MAHASISWA FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - , Nur Hayati, dr, Dra. Yayi Suryo Prabandari, MSi., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background. Learning is a function of mental activities that consists of encoding, storing and retrieving knowledge. The student can enhance these activities and gain better educational achievement if they use the learning skills. Objective. The purpose of this study is to investigate the relationship between perception of learning skills and academic achievement of student at Faculty of Medicine and Health Science, University of Muhammadiyah Yogyakarta. Method. The design of this study was a cross sectional study. One hundred and forty five students participated in this survey. The students were asked to fill in Learning Skill Questionnaire containing 8 items on textbooks reading